2021
DOI: 10.3390/a14030091
|View full text |Cite
|
Sign up to set email alerts
|

UAV Formation Shape Control via Decentralized Markov Decision Processes

Abstract: In this paper, we present a decentralized unmanned aerial vehicle (UAV) swarm formation control approach based on a decision theoretic approach. Specifically, we pose the UAV swarm motion control problem as a decentralized Markov decision process (Dec-MDP). Here, the goal is to drive the UAV swarm from an initial geographical region to another geographical region where the swarm must form a three-dimensional shape (e.g., surface of a sphere). As most decision-theoretic formulations suffer from the curse of dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The central controller can be on the ground, a UAV in the swarm, or a manned aerial vehicle. UAV swarms can adopt different shapes in the air [ 32 ] and can be equipped with the ability to integrate and disintegrate in the air when required. UAV swarms can be used as airborne assets that can provide better situational awareness [ 33 ].…”
Section: Challenges and Threats From Malicious Uavsmentioning
confidence: 99%
See 1 more Smart Citation
“…The central controller can be on the ground, a UAV in the swarm, or a manned aerial vehicle. UAV swarms can adopt different shapes in the air [ 32 ] and can be equipped with the ability to integrate and disintegrate in the air when required. UAV swarms can be used as airborne assets that can provide better situational awareness [ 33 ].…”
Section: Challenges and Threats From Malicious Uavsmentioning
confidence: 99%
“…UAV swarms can adopt different shapes in the air [ 32 ] and can be equipped with the ability to integrate and disintegrate in the air when required.…”
Section: Challenges and Threats From Malicious Uavsmentioning
confidence: 99%
“…The combination of cost structure & revenue structure model is given below which will provide the reader clearidea to understand the calculation. The profit can be fluctuated on the change on business performance (Azam et al, 2021). Here the author tries to give the general view of profitability.…”
Section: Profit Modelmentioning
confidence: 99%
“…Researchers have reported that XaaS can reduce data warehousing problems as well as problems with the use of cloud-based environments and thus address the problem of vendor locking (Chimakurthi, 2021b). In addition, it simplifies the decision-making process using a framework designed to move cloud-enabled applications from one cloud to another and provides basic ways to help organizations find the best cloud provider in the market place (Azam et al, 2021). One study said that XaaS provides more efficient network performance and its ability to achieve flexible behavior for service providers and demanders (Bano et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%